Aβ25-35-based recombinant gene vaccine effectively improves cognitive dysfunction in Alzheimer′s disease mouse models - XIAO Fangyan, LI Wenhua, YANG Nan, HUANG Wei, LIU Yanyong (Jichu yixue yu linchuang)
Objective To investigate the therapeutic effects of a newly constructed Aβ25-35-based recombinant gene vaccine for Alzheimer′s disease (AD). Methods The pcDNA-Aβ25-35-GRP94 recombinant gene vaccine was constructed using Aβ25-35 as the epitope and pcDNA3.1 plasmid as the vector. Early APP/PS1 double-transgenic mice were selected as experimental subjects, including the AD control group and the pcDNA-Aβ25-35-GRP94 immunized group for regular immunization. ELISA was performed to detect the titers and isotypes of Aβ-specific antibodies; Morris Water Maze (MWM) Test and Open-Field Test (OFT) were performed to determine the changes in both cognitive ability and mental state of mice; Immunohistochemistry was used to assess the effects of the vaccine on both Aβ plaques and glial cells in the brains of AD mouse models; ELISA kit was used to evaluate the level of inflammatory factors (TNF-α, IL-1β) in the mouse brain. Results Compared with the AD control group, the pcDNA-Aβ25-35-GRP94 vaccine induced APP/PS1 mice to produce higher levels of Aβ specific antibodies(P＜0.05), and mainly induced IgG1 antibodies (P＜0.01). The vaccine significantly reduced Aβ plaques in the brain tissue(P＜0.05) and effectively alleviated learning memory impairment in APP/PS1 mice (P＜0.05) without causing mental behavioral abnormalities. Moreover, the vaccine inhibited the abnormal proliferation of glial cells (P＜0.05) and did not cause obvious inflammatory reactions in the brain, suggesting the vaccine was safe and effective. Conclusions Early vaccination with a Aβ25-35-based recombinant gene vaccine can induce the formation of high level of Aβ specific antibodies, effectively alleviate the learning memory impairment of AD and related neuro-pathological changes. It may be used to treat AD.